The gravity model of international trade: econometric properties and applications - Cain, Donneil (2017)
This thesis reviews the literature, simulates and applies the Gravity Model of International Trade. The gravity model is widely used in international trade to examine trade ﬂows within a network of exporters and importers. It describes the push and pull factors of trade ﬂows and is fast becoming the most favoured tool when estimating the welfare eﬀects of a trade policy. Therefore, estimating an accurate baseline equation is critical to correctly identify the welfare eﬀects of trade and accompanying trade policies. Recent developments in the literature on the gravity model have helped in this regard. Chapter 1 presents a summary. The literature identiﬁes several estimation issues and prescribes several actions that could be taken to best estimate the gravity model and minimize potential bias in the coeﬃcient(s) of interest. With the objective of minimizing the bias on the coeﬃcient(s) of interest, this thesis, in Chapter 2, builds on the literature by simulating and estimating the gravity model using varying assumptions about the data generating process (dgp) of the errors, conditional mean and sample. The ﬁndings from these simulations are then used to guide the application (Chapter 3) of the gravity model to trade among Caribbean Community (CARICOM) members and trade between CARICOM members and the rest of the world (ROW). Subsequently, in Chapter 4, the gravity model is used as the basis for a general equilibrium framework to investigate the importance of international borders, regional trade agreements (RTAs) and the potential impact of deeper integration in the form of a currency union among CARICOM members. The welfare implications for CARICOM members, associated with being a member of the RTA and adapting a common currency, are presented in Chapter 4 along with several recommended trade policies and areas for future research.